PUBLIC ADMINISTRATION IN THE FIELD OF RENEWABLE ENERGY OF UKRAINE: THE KEY TRENDS AND WAYS OF FURTHER DEVELOPMENT - Stoian O.Iu. (Pressing Problems of Public Administration, 2015)
The main approaches to the definition of the concept of “public administration” areinvestigated. The condition, features and trends of public administration’s development inUkraine in general and in the sphere of renewable energy in particular are researched. The basicsteps of the government of Ukraine towards the development of public administration in thestudied area are analyzed. The further prospects of development of the mechanisms of stateregulation in the sphere of renewable energy of Ukraine in the context of development of publicadministration as the main driving force of effective functioning of the system of public authoritiesin the field of renewable energy in Ukraine are defined in the article.